2021
DOI: 10.1530/jme-20-0210
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the mouse BAT transcriptome reveals a role of progesterone

Abstract: Brown adipose tissue (BAT) is a metabolically active organ that exhibits sex-differential features, i.e., being generally more abundant and active in females than in males. Although sex steroids, particularly estrogens, have been shown to regulate BAT thermogenic function, the underlying molecular mechanisms contributing to sexual dimorphism in basal BAT activity have not been elucidated. Therefore, we assessed the transcriptome of interscapular BAT of male and female C57BL/6J mice by RNA sequencing and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
(68 reference statements)
0
12
1
Order By: Relevance
“…However, in vitro studies of the effects of progesterone on murine brown adipocytes have provided contradictory results. While our study and others showed that progesterone reduced basal Ucp1 mRNA expression and inhibited norepinephrine-stimulated Ucp1 mRNA expression and lipolysis in cultured male and female brown adipocytes (43,127), other studies showed that progesterone had a stimulatory effect on these parameters (115,124). In part, these conflicting results can be explained by the difference in progesterone concentrations used, with high concentrations having an inhibitory effect.…”
Section: Effects Of Progesterone On Batcontrasting
confidence: 85%
See 4 more Smart Citations
“…However, in vitro studies of the effects of progesterone on murine brown adipocytes have provided contradictory results. While our study and others showed that progesterone reduced basal Ucp1 mRNA expression and inhibited norepinephrine-stimulated Ucp1 mRNA expression and lipolysis in cultured male and female brown adipocytes (43,127), other studies showed that progesterone had a stimulatory effect on these parameters (115,124). In part, these conflicting results can be explained by the difference in progesterone concentrations used, with high concentrations having an inhibitory effect.…”
Section: Effects Of Progesterone On Batcontrasting
confidence: 85%
“…Mechanistically, it remains to be determined how the effects of progesterone on BAT are mediated. Our results suggest that when progesterone concentrations are high, part of the effects may be driven by the GR (43). Progesterone may also signal through to the MR, which was shown to be expressed in BAT (130).…”
Section: Effects Of Progesterone On Batmentioning
confidence: 58%
See 3 more Smart Citations